A escola na estação meteorológica: a importância da meteorologia no cotidiano humano - Giroto, Daiane Barbosa [UNESP]; Guldoni, Bruna [UNESP]; Tommaselli, José Tadeu Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project developed by the weather station aims to bring knowledge to students and teachers who wish to understand more about the climatic aspects and tools of functional meteorological station, in response to growing concern about the climate that is increasing due to global climate change. Knowledge of weather and climate action is necessary so we can observe its importance and influence in our daily lives, where the teaching of this is paramount, both with respect to surface interaction - atmosphere as well as the middle-man interaction so that we can thus distinguishes transformations occurring between both, and as such affects humans.

O projeto desenvolvido na estação meteorológica visa levar conhecimento aos alunos e professores que desejam compreender um pouco mais sobre os aspectos climáticos e os instrumentos de uma estação meteorologica funcional, em resposta á crescente preocupação com o clima que vem aumentando devido às mudanças climáticas globais. O conhecimento da atuação do tempo e clima faz-se necessário para que possamos observar sua importância e influência em nosso cotidiano, onde o ensino deste é primordial, tanto com relação a interação superfície – atmosfera como também a interação homem-meio, para que possamos assim distinguir as transformações que ocorrem entre as ambas e como estas atinge os seres humanos.
Keywords: Meteorology; Weather and climate; Tools; Meteorologia; Clima e tempo; Instrumentos